APLIKASI PENGOLAHAN DATA PUSKESMAS (PUSAT KESEHATAN MASYARAKAT) DESA MARGODADI KAB. TULANG BAWANG BARAT - Achmad Nuzul Mariyus; Neni Purwati; RZ Abdul Aziz (Institut Informatika dan Bisnis Darmajaya, 2019)
Health care community is one of the social facilities that uses the developing information technology. The development of this information technology can be seen on the development of clinics and hospitals because they have developed the computerized systems. The access to the contents of the data is done by computerizing so that it will facilitate the data processing, saving time, effort and costs. The method used in this research was through Waterfall. This Waterfall method consisted of communication, planning, modeling, construction, deployment. The data collecting techniques used in this research were interview, observation and literature study. The implementation of this method was by the system analysis, the context diagram, the DFD, and the table relationships. To design and create this application used Netbeans 7.1.2, Java programming languages, MySql databases, and Xampp Webserver, The implementation of this application for the data management of the community health center in the Margodadi Village was able to help the data recording, the data processing, and the report making done by the staffs so that the administrators were able to search the data in this application. Keywords: Information System; Community Health Service Margodadi; Waterfall